The impact of Chinese competition on Africa’s manufacturing - (:unkn) unknown (My University, 2015)
In this paper, the impact of Chinese competition on Africa’s manufacturing value added isanalyzed through a model of manufacturing. Using panel data on 44 African countriescovering the period 2000 to 2013, and controlling for the usual determinants ofindustrialization – such as the size of the domestic market, the quality of infrastructure andgovernance – we find that exports of manufactured goods by China and other countries toAfrican countries mainly exert a negative effect on African manufacturing, while a moderatereal appreciation of African currencies vis-à-vis the renminbi positively influencesmanufacturing value added, probably due to the reduced cost of imported machine andtransport equipment from China (which accounted for 36% of total African imports fromChina in 2013) and to the reduced price of imported consumption goods increasing theremuneration of poor workers and therefore improving their productivity. However, a strongreal appreciation (of more than 33%) instead exerts a negative effect on African’smanufacturing, as traditional theory predicts.
Keywords: African Research